PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA MATERI SISTEM PERNAPASAN TERHADAP IX-6 SMP NEGERI 6 MEDAN TAHUN AJARAN 2016/2017 - Yanti, Yanti (Universitas Dharmawangsa, 2021)
The purpose of this study was to determine whether or not there was an increase in the learning outcomes of Respiratory System Biology through the Think Pair Share (TPS) Cooperative Learning Model for class IX-6 SMP Negeri 6 Medan in the 2016/2017 academic year. This research is Classroom Action Research (CAR). Classroom action research, namely Classroom Action Research. The place of this research is in SMP Negeri 6 Medan class IX-6 Semester II 2016/2017 Academic Year. Of the 32 students in the second cycle, 94% were declared complete, while 2 students had not experienced completeness, 6% with an average score of 87.33. Thus, in the second cycle, the author concludes that the student's score has reached the KKM value. This research is discontinued and does not need to be continued to the next cycle. Based on the results of this study, it can be concluded that the Think Pair Share (TPS) Cooperative Learning Model has an effect on learning outcomes and there is an increase in biology learning outcomes for students in class IX-6 SMP Negeri 6 Medan in the 2016/2017 academic year.